Multifaceted roles of HEAT SHOCK PROTEIN 90 molecular chaperones in plant development - Tichá, Tereza; Samakovli, Despina; Kuchařová, Anna; Vavrdová, Tereza; Šamaj, Jozef (Journal of experimental botany, 2020)
HEAT SHOCK PROTEINS 90 (HSP90s) are molecular chaperones that mediate correct folding and stability of many client proteins. These chaperones act as master molecular hubs involved in multiple aspects of cellular and developmental signalling in diverse organisms. Moreover, environmental and genetic perturbations affect both HSP90s and their clients, leading to alterations of molecular networks determining respectively plant phenotypes and genotypes and contributing to a broad phenotypic plasticity. Although HSP90 interaction networks affecting the genetic basis of phenotypic variation and diversity have been thoroughly studied in animals, such studies are just starting to emerge in plants. Here, we summarize current knowledge and discuss HSP90 network functions in plant development and cellular homeostasis.
Keywords: molekulární chaperony; plant development; protein kinase; fenotyp; Phenotype; Genotype; proteiny tepelného šoku HSP90; co-chaperone; Plant Development; Molecular Chaperones; HEAT SHOCK PROTEIN 90; Chaperone; HSP90 Heat-Shock Proteins; plant cell; Animals; zvířata; genotyp; vývoj rostlin; client protein